MEASUREMENT OF VISCOSITY USES AN ALTERNATIVE VISCOMETER - Oktabella Regina; Hendar Sudrajad; Dina Syaflita (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2018)
Physics learning for fluids can be done by practical methodes in orther the students really understand about the fluids concepts. One of the fluids learning that needs to be practice is about viscosity. Measuring instrument used to determine the viscosity of a liquid is a viscometer. This viscosity measuring instrument can measure the thickness of a fluids accurately and specifically in accordance with predetermined standards. Due to the importance of the amount of viscosity, it is necessary to know the measurement method easily, cheaply and thoroughly. One way that can be used is to use an alternative viscometer as a measure of fluids viscosity. The purpose of this research is to produce an alternative viscometer that can measure the viscosity of a fluids. The type of this research is research and development, namely developing and measuring with an alternative viscometer. This research results that the measurement with an alternative viscometer for several liquids with different viscosity, gets a value that is not much different from the standard viscosity measurement results. The conclusion of the results of this research is that an alternative viscometer can be used to determine the viscosity of a liquid.